Effect of feed additive supplementation on bovine subclinical mastitis - Lamari, Imane (Array, 2021)
Bovine mastitis is an important commercial and sanitary cost in milk production. The prevention and treatment of this disease is essentially based on the use of antibiotics that have limited effectiveness and can negatively affect milk quality. The aim of this study was to evaluate the effectiveness of an alternative treatment based on a symbiotic in the control and prevention of subclinical mastitis (SCM), and in the improvement of the quality of milk produced on a dairy farm in north-central Algeria. The milk of 68 cows was collected and analysed by somatic cell count and bacteriological analysis. Three samples were taken at one-month intervals. The first sample was taken before the administration of a feed additive (SYMBIOVEBA®) to lactating dairy cows. Animals were divided into two groups to study the effects (curative and preventive) of the symbiotic. Each group was further divided into two subgroups, where one received the symbiotic and the other was the control. The prevalence of subclinical mastitis at this farm was 33.82%. Bacterial identification was performed using classical methods only on the group of cows with mastitis; a total of 13 bacterial species were isolated from the three samples. Staphylococci were dominant, with a frequency of 45%, followed by Enterobacteriaceae (40%). These rates were considerably lower in both subgroups, though treated cows showed 100% cure rate for both Staphylococci and Enterobacteriaceae.